2003
DOI: 10.21273/horttech.13.2.0305
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fertilizer Placement on Plant Quality, Root Distribution, and Weed Growth in Container-grown Tropical Ornamental Plants

Abstract: In two experiments, chinese hibiscus (Hibiscus rosa-sinensis), bamboo palm (Chamaedorea seifrizii), areca palm (Dypsis lutescens), fishtail palm (Caryota mitis), macarthur palm (Ptychosperma macarthurii), shooting star (Pseuderanthemum laxiflorum), downy jasmine (Jasminum multiflorum), plumbago (Plumbago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 1 publication
0
16
0
Order By: Relevance
“…When fertilizer placement methods were combined with the use of herbicides, (oryzalin + oxyfluorfen or pendimethalin + oxyfluorfen), dibbling resulted in 89% to 99% control compared with 82% to 90% for topdressing and 81% to 98% for incorporation methods across all three weed species. Broschat and Moore (2003) reported similar findings; when examining the impact of fertilizer placement on crop growth, weed biomass was either similar to or less in container-grown palms when fertilizers were layered, or placed below the soil surface, compared with incorporation or topdressed placements.…”
Section: Effect Of Production Practices On Weedmentioning
confidence: 62%
See 1 more Smart Citation
“…When fertilizer placement methods were combined with the use of herbicides, (oryzalin + oxyfluorfen or pendimethalin + oxyfluorfen), dibbling resulted in 89% to 99% control compared with 82% to 90% for topdressing and 81% to 98% for incorporation methods across all three weed species. Broschat and Moore (2003) reported similar findings; when examining the impact of fertilizer placement on crop growth, weed biomass was either similar to or less in container-grown palms when fertilizers were layered, or placed below the soil surface, compared with incorporation or topdressed placements.…”
Section: Effect Of Production Practices On Weedmentioning
confidence: 62%
“…), downy jasmine (Jasminum multiflorum Burm F.), plumbago (Plumbago auriculata Lam.) (Broschat and Moore, 2003), gumpo azaleas (Azalea · hybrid 'Gumpo White') (Marble et al, 2012), and several other economically important ornamental species (Altland et al, 2004) compared with topdressing or incorporating at similar rates.…”
Section: Effect Of Production Practices On Weedmentioning
confidence: 99%
“…2, drip-irrigated only, showed that among the CRF placement methods, the calculated amounts of NO 3 -N leached from dibble containers over the duration of the experiment were intermediate for CRF rates (mean, 252 mg/pot; range, 151 to 367 mg/pot) compared with incorporated (mean, 295 mg/pot; range, 151 to 410 mg/ pot) and topdressed (mean, 79 mg/pot; range, 65 to 108 mg/pot). Only a few studies have compared the effectiveness of these three fertilizer placement methods (Altland et al, 2004;Broschat and Klock-Moore, 2003) and no placement methods were pronounced. Responses varied with species, location, and cultural factors (Broschat and Klock-Moore, 2003;Million et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have compared the effectiveness of these three fertilizer placement methods (Altland et al, 2004;Broschat and Klock-Moore, 2003) and no placement methods were pronounced. Responses varied with species, location, and cultural factors (Broschat and Klock-Moore, 2003;Million et al, 2007). Higher plant growth with dibbled CRF also has been reported by Altland et al (2004) for container-grown azalea (Rhododendron sp.…”
Section: Discussionmentioning
confidence: 99%
“…In a container study, Altland et al (2004) reported that dibbling fertilizer (placing fertilizer directly beneath root ball) significantly reduced weed germination compared with incorporating (mixing fertilizer in with media) or top-dressing (placing fertilizer on container media surface). In a similar study, Broschat and Moore (2003) reported less weed growth in container-grown ornamentals when fertilizer was layered just beneath the root ball (a modified dibble) compared with incorporation or topdressing. Few studies investigating the effects of fertilizer placement on weed growth in the landscape have been reported.…”
Section: Other Nonchemical Control Methodsmentioning
confidence: 93%